2000
DOI: 10.1088/0953-4075/33/4/105
|View full text |Cite
|
Sign up to set email alerts
|

Counting cold collisions

Abstract: We have experimentally explored a novel possibility to study exoergic cold atomic collisions. Trapping of small countable atom numbers in a shallow magneto-optical trap and monitoring of their temporal dynamics allows us to directly observe isolated two-body atomic collisions and provides detailed information on loss statistics. A substantial fraction of such cold collisional events has been found to result in the loss of one atom only. We have also observed for the first time a strong optical suppression of g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…In the simulation, one has to choose whether a collision ejects both atoms from the trap, or only one; good agreement with the experiment is obtained by assuming that in the collision both atoms are ejected from the trap (otherwise, we would reach an average number of atoms 0.5 < N < 1, contrary to the experiment). This is also consistent with what is expected from the underlying collisional mechanisms, even if one-atom losses have also been observed in other geometries [12]. In order to get quantitative predictions, one has to introduce numerical values for γ and β .…”
Section: Collisional Blockadesupporting
confidence: 84%
“…In the simulation, one has to choose whether a collision ejects both atoms from the trap, or only one; good agreement with the experiment is obtained by assuming that in the collision both atoms are ejected from the trap (otherwise, we would reach an average number of atoms 0.5 < N < 1, contrary to the experiment). This is also consistent with what is expected from the underlying collisional mechanisms, even if one-atom losses have also been observed in other geometries [12]. In order to get quantitative predictions, one has to introduce numerical values for γ and β .…”
Section: Collisional Blockadesupporting
confidence: 84%
“…Typically, cold atoms are loaded into a FORT from a MOT, which utilizes red-detuned light beams. Studies of individual collisional loss events in a MOT with high gradient magnetic field has shown that about 10 percent of collisional loss events are 2 − 1 loss [48].…”
Section: Two-atom Light-assisted Collisions Induced By Red-detuned Lightmentioning
confidence: 99%
“…When N 2 = 0, we recover the phenomenological equation sometimes used to describe the loading of a trap containing a small number of atoms [21,24], i.e., dN/dt = R − γ N − β N (N − 1). When N 2 = N (i.e., assuming a Poisson distribution), Eq.…”
mentioning
confidence: 99%